MANAJEMEN KEUANGAN DAN KEPUASAN KEUANGAN ISTRI PADA KELUARGA DENGAN SUAMI ISTRI BEKERJA - Hakim, Fitri Apriliana; Sunarti, Euis; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2014)
The purpose of this study was to analyze the influence of family characteristics and financial management on wife financial satisfaction. The research design was a cross sectional of 120 wives from dual earner families whose last child aged 0-6 years old. Samples selected by using nonproportional stratified random sampling technique in Bogor District of West and Central Bogor. The location determined by purposive because represented high density of population with low income and education level. The result of this study found that a quarter wives had good management and one of ten had high level of financial satisfaction. Financial management negatively correlated with wife’s age, family size, length of marriage, and positively correlated with wife’s education, per capita family income, and values of the asset. Financial management and wife’s education had positively significant influenced on wife financial satisfaction. Knowledge of financial management is needed to give to families with low income and low education levels to attain financial satisfaction.